2007
DOI: 10.1002/chem.200601559
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Attachment of Gold and Poly(lactic acid) Nanoparticles onto ω‐Aminoalkanoic Acid Self‐Assembled Monolayers on 316L Stainless Steel

Abstract: The assembly of poly(lactic acid) (PLA) nanoparticles on a 12-aminodecanoic acid (ADA) self-assembled monolayer (SAM) is described. Assembly is accomplished through electrostatic interactions between the positively charged SAM and the negatively charged PLA nanoparticles. The strategy used involves two steps in which a preliminary electrochemical coating of the ADA SAM is followed by a second step that involves immersing the SAM in a solution containing gold or PLA nanoparticles. The SAM was characterized by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Moreover, a significant difference in the AuNP packing density can be observed between 30% and 45% quaternized q P2VP domains, proving an increased AuNP adsorption with higher becoming θ quaternization . Similar results gained from resembling systems were reported by Cant et al, Lau et al, and Shustak et al Note here, that EIS measurements revealed each individual block copolymer film to require somewhat different durations to reach impedance equilibration upon the different fluid injections. However, impedance balancing is crucial to serve as reference point for following fluid injections and to ensure full charge neutralization at the film|electrolyte interface during AuNP solution injection as well as to observe significant distinctions in particle packing density after measurement.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Moreover, a significant difference in the AuNP packing density can be observed between 30% and 45% quaternized q P2VP domains, proving an increased AuNP adsorption with higher becoming θ quaternization . Similar results gained from resembling systems were reported by Cant et al, Lau et al, and Shustak et al Note here, that EIS measurements revealed each individual block copolymer film to require somewhat different durations to reach impedance equilibration upon the different fluid injections. However, impedance balancing is crucial to serve as reference point for following fluid injections and to ensure full charge neutralization at the film|electrolyte interface during AuNP solution injection as well as to observe significant distinctions in particle packing density after measurement.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Similar behavior was recorded for AUDT SAM, which was quite unexpected since the −NH 2 group is generally considered to be suitable to bind metal (e.g. Au) NPs by electrostatic attraction between the particles and film surfaces 52, 61. However, it appeared to be non‐effective for the binding of the Co NPs in the given case, even though the suspension of NPs was acidic and the terminal −NH 2 groups of the SAM could be protonated readily.…”
Section: Resultssupporting
confidence: 65%
“…The binding of the NPs to the AUDT-, TPDMT-, and PPPT-containing SAMs and chemical templates occurred over different mechanisms depending on the character of the terminal (tail) group. In particular, in the case of amino (AUDT) and pyridine (PPPT) termination, the NPs were presumably immobilized via electrostatic interaction . Indeed, the pH of the fabricated gold colloid solution was around 5, so that the amine and pyridine tail groups of the respective SAMs were expected to be protonated and thus carrying a positive charge when exposed to the suspension of NPs which in turn, as mentioned above, were charged negatively.…”
Section: Resultsmentioning
confidence: 99%